Adverse Events Associated With Treatment of Tripterygium wilfordii Hook F: A Quantitative Evidence Synthesis - Ru, Yi; Luo, Ying; Zhou, Yaqiong; Kuai, Le; Sun, Xiaoying; Xing, Meng; Liu, Liu; Lu, Yi; Hong, Seokgyeong; Chen, Xi; Song, Jiankun; Luo, Yue; et al. (Frontiers in Pharmacology, 2019)
Background: Tripterygium wilfordii Hook F (TwHF) can cause adverse reactions (AEs) in clinical application and may be harmful to human health. To summarize the AEs caused by Tripterygium wilfordii tgpolyglycoside (TWP), the most common preparation of TwHF for clinical use. Methods: The Cochrane Library, EMBASE, PubMed, and Web of Science were searched to identify potential articles on this topic. All single-arm trials, controlled clinical trials (CCTs), and randomized controlled trials (RCTs) were selected and summarized. Meta-regression was used to determine the sources of heterogeneity and subgroups were used to identify factors leading to AEs. Results: Forty-six studies, comprising 25 RCTs, 13 CCTs, and 8 single-arm trials, were included in this meta-analysis, representing 2437 enrolled TWP-treated participants. Combined intervention, drug dosage, medication treatment, pharmaceutical manufacturers, and specific organ toxicity were identified as potential factors leading to TWP-induced AEs in this meta-analysis. In patients treated with TWP, the global incidence of AEs was 30.75% (95% CI [21.18‒40.33], I2 = 97%) and that of severe grade AEs was 4.68% (95% CI [0.00–12.72], I2 = 53%). Organ-specific analyses indicated that TWP treatment elicited intestinal toxicity, reproductive toxicity, hepatotoxicity, nephrotoxicity, hematotoxicity, cutaneous toxicity, and other damages. The AEs analyzed in the subgroups of combined intervention, drug dosage, medication treatment, and pharmaceutical manufacturers were considered as primary outcomes, and organic-specific AEs were considered as secondary outcomes. Conclusions: The occurrence of TWP-induced AEs was systemic, organ-specific, and related to medication course, combined intervention, and drug dosage.